Implementation of Virtual Mouse Using Pupil Detection for Physically Disabled - Gnana Prasuna, K; Harshitha, M; Chaitanya Deepti, G; Shalini, K; Baby, B (International Journal of Computer Sciences and Engineering, 2023)
Current technology often uses the computer mouse or finger to move the cursor along the screen. A mouse or finger movement is detected by the system and mapped to the cursor movement. HCI (Human-Computer Interface) involves the use of computer technology to provide a human-computer interface. Communication between humans and computers needs to be made more effective through appropriate technology. Interaction between humans and computers is crucial. It is therefore important to find a method for enabling individuals with disabilities to communicate with computers and be part of the Information Society in an equal way. In this project, a virtual mouse is built that works based upon the movement of the pupil of an eye, where the detection takes place with the help of a webcam. Here, the system detects the face of the user using facial landmark detectors. Then using the Canny Edge detection algorithm, the pupil of the eye is detected. Then the mouse is calibrated to the pupil. Left click and right click are implemented by detecting left blink and right blink of eye using Eye Aspect Ratio algorithm. The system is expected to be easy to use, take fast input, and work as an alternative to a physical mouse.